1997
DOI: 10.1111/1523-1747.ep12292572
|View full text |Cite
|
Sign up to set email alerts
|

Agouti Signaling Protein Inhibits Melanogenesis and the Response of Human Melanocytes to α-Melanotropin

Abstract: In mouse follicular melanocytes, the switch between eumelanin and pheomelanin synthesis is regulated by the extension locus, which encodes the melanocortin-1 receptor (MC1R) and the agouti locus, which encodes a novel paracrine-signaling molecule that inhibits binding of melanocortins to the MC1R. Human melanocytes express the MC1R and respond to melanotropins with increased proliferation and eumelanogenesis, but a potential role for the human homolog of agouti-signaling protein, ASIP, in human pigmentation ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
145
0
9

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(167 citation statements)
references
References 29 publications
13
145
0
9
Order By: Relevance
“…ASP is an antagonist of the melanocortin 1 receptor, which plays a key role in regulating pigmentation (21). ASP inhibits melanin formation in mouse melanocytes and in melanoma cells as well as in NHM (22)(23)(24). We treated NHM obtained from neonatal moderately pigmented (n-MP) skin with ASP.…”
Section: Sox9 Is Expressed In Melanocytes In Vivomentioning
confidence: 99%
“…ASP is an antagonist of the melanocortin 1 receptor, which plays a key role in regulating pigmentation (21). ASP inhibits melanin formation in mouse melanocytes and in melanoma cells as well as in NHM (22)(23)(24). We treated NHM obtained from neonatal moderately pigmented (n-MP) skin with ASP.…”
Section: Sox9 Is Expressed In Melanocytes In Vivomentioning
confidence: 99%
“…Agouti signaling protein antagonizes the action of ␣-melanocyte-stimulating hormone and inhibits eumelanin synthesis and tyrosinase activity. 7 It may be applicable to humans because the messenger RNA for agouti signaling protein is expressed in various human tissues. 8 Although we failed to detect the messenger RNA for agouti signaling protein from the biopsy specimens by polymerase chain reaction (data not shown), it may be possible that melanocytes in the hair bulb of this patient produced pheomelanin and eumelanin alternatively, resulting in alternative segmentation of hair shafts.…”
Section: Commentsmentioning
confidence: 99%
“…16 Most studies have proposed that ASP acts by antagonizing the action of a-MSH at MC1R, resulting in decreased cell tyrosinase concentrations leading to suppression of eumelaninogenesis. 6,9 In this study, depigmentation in the rats started as early as day 3 after the pCMV-hASP gene was delivered to their skin using the gene gun ( Figure 1). The effect was most prominent on day 14, but gradually returned to original pigmentation by day 28.…”
Section: Discussionmentioning
confidence: 86%
“…In vitro studies have shown that human ASP acts in a similar fashion to mouse agouti protein, in that it downregulates melanogenic genes controlling eumelanin synthesis in human melanocytes, and its in vivo expression in transgenic mice gives rise to yellow coat colours. [7][8][9][10] Thus, it appears that the ASP plays an important role in the regulation of mice and human skin pigmentation and hair colour.…”
Section: Introductionmentioning
confidence: 99%